Design and selection of peptides to block the SARS-CoV-2 receptor binding domain by molecular docking - Ramirez-Acosta, Kendra; Rosales-Fuerte, Ivan A.; Perez-Sanchez, J. Eduardo; Nuñez-Rivera, Alfredo; Juarez, Josue; Cadena-Nava, Ruben D. (Beilstein Journal of Nanotechnology, 2022)
The novel Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) is currently one of the most contagious viruses in existence and the cause of the worst pandemic in this century, COVID-19. SARS-CoV-2 infection begins with the recognition of the cellular receptor angiotensin converting enzyme-2 by its spike glycoprotein receptor-binding domain (RBD). Thus, the use of small peptides to neutralize the infective mechanism of SARS-CoV-2 through the RBD is an interesting strategy. The binding ability of 104 peptides (University of Nebraska Medical Center’s Antimicrobial Peptide Database) to the RBD was assessed using molecular docking. Based on the molecular docking results, peptides with great affinity to the RBD were selected. The most common amino acids involved in the recognition of the RBD were identified to design novel peptides based on the number of hydrogen bonds that were formed. At physiological pH, these peptides are almost neutral and soluble in aqueous media. Interestingly, several peptides showed the capability to bind to the active surface area of the RBD of the Wuhan strain, as well as to the RBD of the Delta variant and other SARS-Cov-2 variants. Therefore, these peptides have promising potential in the treatment of the COVID-19 disease caused by different variants of SARS-CoV-2. This research work will be focused on the molecular docking of peptides by molecular dynamics, in addition to an analysis of the possible interaction of these peptides with physiological proteins. This methodology could be extended to design peptides that are active against other viruses.
Keywords: angiotensin converting enzyme-2 (ACE2); antiviral peptides; hydrogen bonds; molecular docking; SARS-CoV-2 RBD

Coronavirus Disease (COVID-19) Situation Reports

(untitled) - Tortorici, M. A.; Veesler, D. (Adv. Virus Res., 2019)

(untitled) - Walls, A. C.; Park, Y.-J.; Tortorici, M. A.; Wall, A.; McGuire, A. T.; Veesler, D. (Cell, 2020)

(untitled) - He, Y.; Zhou, Y.; Liu, S.; Kou, Z.; Li, W.; Farzan, M.; Jiang, S. (Biochem. Biophys. Res. Commun., 2004)

(untitled) - Shang, J.; Ye, G.; Shi, K.; Wan, Y.; Luo, C.; Aihara, H.; Geng, Q.; Auerbach, A.; Li, F. (Nature, 2020)

(untitled) - Othman, H.; Bouslama, Z.; Brandenburg, J.-T.; da Rocha, J.; Hamdi, Y.; Ghedira, K.; Srairi-Abid, N.; Hazelhurst, S. (Biochem. Biophys. Res. Commun., 2020)

(untitled) - Morgan, D. C.; Morris, C.; Mahindra, A.; Blair, C. M.; Tejeda, G.; Herbert, I.; Turnbull, M. L.; Lieber, G.; Willett, B. J.; Logan, N.; Smith, B.; Tobin, A. B.; et al. (Pept. Sci., 2021)

(untitled) - Barh, D.; Tiwari, S.; Silva Andrade, B.; Giovanetti, M.; Almeida Costa, E.; Kumavath, R.; Ghosh, P.; Góes-Neto, A.; Carlos Junior Alcantara, L.; Azevedo, V. (F1000Research, 2020)

(untitled) - Berkhout, B.; van Wamel, J. L. B.; Beljaars, L.; Meijer, D. K. F.; Visser, S.; Floris, R. (Antiviral Res., 2002)

(untitled) - Cole, A. M. (Expert Opin. Ther. Targets, 2003)

(untitled) - Ng, T. B.; Cheung, R. C. F.; Wong, J. H.; Wang, Y.; Ip, D. T. M.; Wan, D. C. C.; Xia, J. (Appl. Microbiol. Biotechnol., 2015)

(untitled) - Shah, V. K.; Firmal, P.; Alam, A.; Ganguly, D.; Chattopadhyay, S. (Front. Immunol., 2020)

(untitled) - Doneva, N.; Doytchinova, I.; Dimitrov, I. (Symmetry, 2021)

(untitled) - Basit, A.; Karim, A. M.; Asif, M.; Ali, T.; Lee, J. H.; Jeon, J. H.; Rehman, S. u.; Lee, S. H. (Front. Pharmacol., 2021)

(untitled) - Han, Y.; Král, P. (ACS Nano, 2020)

Computational Design of Ligand Binding Proteins - Roche, D. B.; McGuffin, L. J. (In Silico Identification and Characterization of Protein-Ligand Binding Sites, 2016)

(untitled) - Pagadala, N. S.; Syed, K.; Tuszynski, J. (Biophys. Rev., 2017)

(untitled) - Hadley, E. B.; Hancock, R. E. W. (Curr. Top. Med. Chem., 2010)

Molecular Modeling of Proteins - Morris, G. M.; Lim-Wilby, M. (Molecular Docking, 2008)

(untitled) - Pantsar, T.; Poso, A. (Molecules, 2018)

(untitled) - Eberhardt, J.; Santos-Martins, D.; Tillack, A. F.; Forli, S. (J. Chem. Inf. Model., 2021)

(untitled) - Wang, G.; Li, X.; Wang, Z. (Nucleic Acids Res., 2016)

(untitled) - Wang, G.; Li, X.; Wang, Z. (Nucleic Acids Res., 2009)

(untitled) - Wang, Z. (Nucleic Acids Res., 2004)

(untitled) - Qiao, B.; Olvera de la Cruz, M. (ACS Nano, 2020)

(untitled) - Wiesner, J.; Vilcinskas, A. (Virulence, 2010)

(untitled) - Mandal, S. M.; Silva, O. N.; Franco, O. L. (Drug Discovery Today, 2014)

(untitled) - Roy, A.; Kucukural, A.; Zhang, Y. (Nat. Protoc., 2010)

(untitled) - Yang, J.; Zhang, Y. (Nucleic Acids Res., 2015)

(untitled) - Lamiable, A.; Thévenet, P.; Rey, J.; Vavrusa, M.; Derreumaux, P.; Tufféry, P. (Nucleic Acids Res., 2016)

(untitled) - Shen, Y.; Maupetit, J.; Derreumaux, P.; Tufféry, P. (J. Chem. Theory Comput., 2014)

(untitled) - Thévenet, P.; Shen, Y.; Maupetit, J.; Guyon, F.; Derreumaux, P.; Tufféry, P. (Nucleic Acids Res., 2012)

The PyMOL Molecular Graphics System, version 2.0 (Schrödinger, LLC)

(untitled) - Wallace, A. C.; Laskowski, R. A.; Thornton, J. M. (Protein Eng., Des. Sel., 1995)

(untitled) - Ortega, A.; Amorós, D.; García de la Torre, J. (Biophys. J., 2011)

(untitled) - Paul, S.; Sidney, J.; Sette, A.; Peters, B. (Curr. Protoc. Immunol., 2016)

(untitled) - Calis, J. J. A.; Maybeno, M.; Greenbaum, J. A.; Weiskopf, D.; De Silva, A. D.; Sette, A.; Keşmir, C.; Peters, B. (PLoS Comput. Biol., 2013)

(untitled) - Adhikari, U. K.; Tayebi, M.; Rahman, M. M. (J. Immunol. Res., 2018)

(untitled) - Xue, L. C.; Rodrigues, J. P.; Kastritis, P. L.; Bonvin, A. M.; Vangone, A. (Bioinformatics, 2016)

(untitled) - Vangone, A.; Bonvin, A. M. (eLife, 2015)

(untitled) - Honorato, R. V.; Koukos, P. I.; Jiménez-García, B.; Tsaregorodtsev, A.; Verlato, M.; Giachetti, A.; Rosato, A.; Bonvin, A. M. J. J. (Front. Mol. Biosci., 2021)

(untitled) - Tesauro, D.; Accardo, A.; Diaferia, C.; Milano, V.; Guillon, J.; Ronga, L.; Rossi, F. (Molecules, 2019)

(untitled) - Leal, J.; Liu, X.; Peng, X.; Mohanty, R. P.; Arasappan, D.; Wylie, D.; Schwartz, S. H.; Fullmer, J. J.; McWilliams, B. C.; Smyth, H. D. C.; Ghosh, D. (bioRxiv, 2019)

(untitled) - Fei, L.; Ren, L.; Zaro, J. L.; Shen, W.-C. (J. Drug Targeting, 2011)

(untitled) - Arai, S.; Miyazaki, T. (Semin. Immunopathol., 2018)

(untitled) - McNeil, P.; Hohman, T.; Muscatine, L. (J. Cell Sci., 1981)

(untitled) - Chen, D.; Oezguen, N.; Urvil, P.; Ferguson, C.; Dann, S. M.; Savidge, T. C. (Sci. Adv., 2016)

(untitled) - C, S.; S., D. K.; Ragunathan, V.; Tiwari, P.; A., S.; P, B. D. (J. Biomol. Struct. Dyn., 2022)

(untitled) - Kalafatovic, D.; Mauša, G.; Todorovski, T.; Giralt, E. (J. Cheminf., 2019)

(untitled) - Bozovičar, K.; Bratkovič, T. (Int. J. Mol. Sci., 2020)

(untitled) - Lesitha Jeeva Kumari, J.; Jesu Jaya Sudan, R.; Sudandiradoss, C. (PLoS One, 2017)

(untitled) - Qin, C.; Zhou, L.; Hu, Z.; Zhang, S.; Yang, S.; Tao, Y.; Xie, C.; Ma, K.; Shang, K.; Wang, W.; Tian, D.-S. (Clin. Infect. Dis., 2020)

(untitled) - Chiappelli, F.; Khakshooy, A.; Greenberg, G. (Bioinformation, 2020)

(untitled) - Greco, I.; Molchanova, N.; Holmedal, E.; Jenssen, H.; Hummel, B. D.; Watts, J. L.; Håkansson, J.; Hansen, P. R.; Svenson, J. (Sci. Rep., 2020)

(untitled) - Laverty, G.; Gilmore, B. (Microbiol. Infect. Dis., 2014)

(untitled) - Savjani, K. T.; Gajjar, A. K.; Savjani, J. K. (Int. Scholarly Res. Not., 2012)

(untitled) - Ciemny, M.; Kurcinski, M.; Kamel, K.; Kolinski, A.; Alam, N.; Schueler-Furman, O.; Kmiecik, S. (Drug Discovery Today, 2018)

(untitled) - Sacquin-Mora, S.; Prévost, C. (Structure, 2015)

(untitled) - Verschueren, E.; Vanhee, P.; Rousseau, F.; Schymkowitz, J.; Serrano, L. (Structure, 2013)

(untitled) - Jawad, B.; Adhikari, P.; Podgornik, R.; Ching, W.-Y. (J. Chem. Inf. Model., 2021)

(untitled) - Buratto, D.; Saxena, A.; Ji, Q.; Yang, G.; Pantano, S.; Zonta, F. (Front. Immunol., 2021)

(untitled) - Stoddard, S. V.; Wallace, F. E.; Stoddard, S. D.; Cheng, Q.; Acosta, D.; Barzani, S.; Bobay, M.; Briant, J.; Cisneros, C.; Feinstein, S.; Glasper, K.; Hussain, M.; et al. (Biophysica, 2021)

(untitled) - Baig, M. S.; Alagumuthu, M.; Rajpoot, S.; Saqib, U. (Drugs R&D, 2020)